The pesticide hazard : a global health and environmental audit - Dinham, Barbara (London, 1993)
"Pesticides are responsible for some 20,000 deaths and 3 million cases of acute poisoning annually - a burden borne, in particular, by agricultural workers and rural communities worldwide. The industry has felt compelled to respond to the international concern on both health and environmental grounds which gas been expressed, notably by NGOs lobbying for higher safety standards and export controls. This policy-relevant, global survey, based on up-to-date research and data gathered by scientists and local organisations in Latin America, Africa and Asia, as well as information provided by the companies themselves to the EC's Product Stewardship Survey, assesses what progress has been made in both safety and environmental terms since the introduction of the FAO's voluntary Code of Conduct on the Distribution and Use of Pesticides in 1985 and the Prior Informed Consent procedure of 1989.